Digital printing in art: enhancing narrative and expression on contemporary works / Muhammad Yusuf Masod - Masod, Muhammad Yusuf Masod (Faculty of Art and Design, 2024)
This study explores the utilization of digital printing technologies in contemporary art, specifically examining how these technologies influence narrative depth and artistic expression. Using a case study approach, this research adapts findings from previous study to demonstrate that digital technologies significantly enhance artistic expression and narrative complexity. These findings highlight the capability of digital tools to innovate artistic practices and enrich the interpretation and appreciation of art in contemporary society. The implications of this study are valuable for artists, and educators in understanding and leveraging the interplay between technology and art.